MOLECULAR DOCKING OF SPEARMINT PHYTOCOMPOUNDS AGAINST CYP21A2: IMPLICATIONS FOR PCOS THERAPY - MALAKHED, SNEHA (Innovare Journal of Medical Sciences, 2024)
Objectives: In this study, phytocompounds of spearmint that is known to have anti-androgenic activity are docked against a protein CYP21A2. This protein is also known as progesterone complex, one of the member cytochrome P450 enzymes; mutations in the genes encoding these proteins are causative factors of polycystic ovarian syndrome (PCOS). Methods: The study was based on computations using different phytochemicals of spearmint docking to a target protein CYP21A2 which causes hormonal imbalance leading to PCOS and hirsutism. Molecular docking was conducted using PyRx-virtual screening tool and Biovia discovery studio 2.0 to determine binding affinities of different phytochemicals to target protein. Results: The docking result revealed that bicyclogermacrene, cubebol, (-)-beta-bourbonene, alpha-bourbonene, and spathulenol showed highest binding affinities between –8.1 and –8.5 kcal/mol. Further, absorption, distribution, metabolism, excretion, and toxicity properties of these compounds are explored mainly to understand the possibility of developing potential drugs for PCOS. Conclusion: These bioactive compounds can be considered as potential agents that can be used with polyherbal plant extract to reduce the androgen levels in women suffering from PCOS.